Effect of Ethanolic Extract of Mespilus germanica on Cutaneous Leishmaniasis in BALB/c Mice - N Shariatifar; R Rahimnia; AM Jamshidi; M Pirali Hamedani; Sh Shoeibi (Institue of Medicinal Plants, ACECR, 2011)
Background: Leishmaniasis is a vector-borne disease caused by flagellated protozoan parasites of the genus Leishmania, which affects both humans and other mammals. Most of the available drugs against the disease are toxic and some are parasite resistance to them. Objective: The purpose of this study was to examine the effect of Mespilus germanica extract on cutaneous leishmaniasis (CL) in BALB/c Mice. Methods: Ethanolic extract of Mespilus germanica with 40, 60 and 80% concentrations were prepared. Then, the BALB/c mice were inoculated subcutaneously by 0.1 ml liquid phase culture containing promastigotes of Leishmania major. Ethanolic extract of the leaves of Mespilus germanica in different concentrations, were used topically on CL lesions. Results: The mean diameter of the lesions were decreased, and also the number of parasites in the lesions had declined with complete healing by ending the period time of treatment in 4 mice (26.7%), (p< 0.05) and in 9 animals (82%), (p<0.05) respectively, by using the 40% concentration of the extract. Also in a concentration of 60%, mean ulcer diameter decreased, with complete healing in 3 mice (20%), (p<0.001). In this concentration, the mean number of parasites in lesions had declined (66.4%), with total elimination in 8 animals (p< 0.001). Conclusion: We showed that the extract of Mespilus germanica has the highest effectiveness in concentration of 40%, causing greater reductions in both ulcer diameter and the number of parasites in the lesions compared with other prepared concentrations. Therefore, we suggest the use of 40% extract for the treatment of human cases.